método da substituição
25p-13q
15p=4q-7
poty:
Está faltando a igualdade na primeira equação
Respostas
respondido por:
1
{25p - 13q = 1 ---(i)
{15p = 4q-7 --> p = (4q-7)/15
{25 . (4q-7)/15 - 13q = 1
(20q - 35)/3 - 13q = 1 ----mmc=3
20q - 35 - 39q = 3
- 19q = 3 + 35
- 19q = 38
19q = -38
q = -2
(i) 25p - 13q = 1
25p = 1 + 13(-2)
25p = 1 - 26
25p = - 25
p = -1
{15p = 4q-7 --> p = (4q-7)/15
{25 . (4q-7)/15 - 13q = 1
(20q - 35)/3 - 13q = 1 ----mmc=3
20q - 35 - 39q = 3
- 19q = 3 + 35
- 19q = 38
19q = -38
q = -2
(i) 25p - 13q = 1
25p = 1 + 13(-2)
25p = 1 - 26
25p = - 25
p = -1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás